Dynamics Analysis of a Stochastic Plant Disease Model with Continuous Cultural Control Strategy - Haisu Zhang; Tongqian Zhang (Complexity)
In this paper, a new stochastic plant disease model with continuous control strategy is proposed and analyzed. The dynamics of the system are explored under white noise disturbance. We prove that if R1>1, then the disease is persistent; moreover, if R2>1, then the solutions of the system have a stationary distribution. For the special case, we prove that if R1<1, then the disease will eventually disappear. Finally, some numerical simulations were implemented to illustrate the theoretical results.